Regulation of metabolic and transcriptional responses by the thyroid hormone in cellular models of murine macrophages - López-Mateo, Irene; Rodríguez-Muñoz, Diego; de La Rosa, Juan Vladimir; Castrillo, Antonio; Alemany, Susana; Aranda, Ana (Frontiers in Immunology, 2022)
Oncogene-immortalized bone marrow-derived macrophages are considered to be a good model for the study of immune cell functions, but the factors required for their survival and proliferation are still unknown. Although the effect of the thyroid hormones on global metabolic and transcriptional responses in macrophages has not yet been examined, there is increasing evidence that they could modulate macrophage functions. We show here that the thyroid hormone T3 is an absolute requirement for the growth of immortal macrophages. The hormone regulates the activity of the main signaling pathways required for proliferation and anabolic processes, including the phosphorylation of ERK and p38 MAPKs, AKT, ribosomal S6 protein, AMPK and Sirtuin-1. T3 also alters the levels of metabolites controlling transcriptional and post-transcriptional actions in macrophages, and causes widespread transcriptomic changes, up-regulating genes needed for protein synthesis and cell proliferation, while down-regulating genes involved in immune responses and endocytosis, among others. This is not observed in primary bone marrow-derived macrophages, where only p38 and AMPK activation is regulated by T3 and in which the metabolic and transcriptomic effects of the hormone are much weaker. However, the response to IFN- is reduced by T3 similarly in immortalized macrophages and in the primary cells, confirming previous results showing that the thyroid hormones can antagonize JAK/STAT-mediated signaling. These results provide new perspectives on the relevant pathways involved in proliferation and survival of macrophage cell culture models and on the crosstalk between the thyroid hormones and the immune system